Effect of different diets using sewage sludge on the growth performance of the gold fish Carassius auratus - C., Veerabahu; D, Radhika.; R., Felsia; D., Kumar (Malaysian Journal of Science, 2005)
The gold fish Carassius auratus was selected for the present investigation. The growth rate and other parameters of gold fish (18 days old) Carassius auratus juveniles were investigated using four different types of diets for 21 days. The diets were prepared using the sewage sludge after they were treated in two methods namely antibiotic treatment and acid treatment. This was compared with diets prepared from untreated (raw) sewage sludge and conventional feed (without sewage sludge). The juveniles fed with acid treated sewage sludge showed the best growth rate of 0.194 g, and specific growth rate of 0.685%/ day and FCR (%) of 0.027, while other diets of untreated sludge, conventional feed, and antibiotic treated sludge showed minimum growth rates of 0.069 g, 0.067 g, and 0.129g respectively. Acid-treated sludge feed showed the best gross growth efficiency, net growth efficiency, relative growth efficiency and FCR (%) of 4.232, 4.455, 0.040 and 0.027, respectively. Antibiotic treated sludge feed showed the best assimilation efficiency of 95.8%. Untreated sludge feed showed the assimilation, metabolism and contractory consumption (C) rate of 4.60%,4.482, and 4.998, respectively, for 21 days.